MODEL PEMBELAJARAN SHALAT BERJAMAAH UNTUK INTERNALISASI DISIPLIN ANAK DI TARBIYATUL AULAD NURUS SUNNAH PEMALANG - Epy Pujiaty; Budi Hartati (Berajah Journal, 2026)
Building discipline in young boys often faces challenges due to high levels of motor activity which, if not properly managed, can hinder the learning process. This study aims to analyze the process of internalizing discipline in Group B boys through the congregational prayer (shalat berjamaah) learning model at Tarbiyatul Aulad (TA) Nurus Sunnah Pemalang, focusing on the 'Imam Cilik' (Young Imam) strategy as an educational instrument to channel motor energy into self-control and responsibility. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and character development documentation. The results reveal that rotating the 'Imam Cilik' role effectively manages children's physical energy positively through three phases of internalization: mimetic (imitation of movements), identification (reduction of impulsivity through the moral weight of the role), and autonomy (independent awareness). The findings show that the discipline formed is generalized to activities outside of prayer, where children who initially exhibited undirected motor activity became calmer and more responsible. The study concludes that the 'Imam Cilik' model is effective in transforming motor energy into a foundation for leadership character and autonomous discipline in boys.